The Role of Information Literacy in Mitigating the Spread of Hoaxes on Social Media - Kurniasih, Erni; Damayani, Ninis Agustini; Zubair, Feliza (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
The rapid proliferation of hoaxes on social media presents a significant societal challenge due to their potentially severe impacts. It is widely accepted that information literacy protects society from hoaxes. Recognizing the protective role of information literacy against hoaxes, this study investigates the influence of information literacy on the ability to identify hoaxes and the intention to share them via social media. Employing a quantitative research methodology, the study utilized a survey through Google Forms. The questionnaire was disseminated via social media to a purposive sample of 100 active social media users in Indonesia, ensuring a diverse representation across various age groups and educational backgrounds. The findings indicate that individuals with higher levels of information literacy demonstrate a greater capacity to identify hoaxes accurately and exhibit a diminished propensity to share them. These results highlight the critical importance of information literacy in combating the spread of hoaxes on social media. The study provides valuable insights for policymakers and educators in developing strategies to enhance information literacy within the community.